Environmental impact assessment of an ecological park-type cemetery - Espinoza Eche, José Jorge (2001)
Cemeteries may constitute a danger to the environment and people 's health if not properly controlled mineralization of the organic parts of the human remains, leading to the formation of unpleasant odors and substances soluble carriers of pathogens , and allowed to be perceived by the people seated in the environment and / or liquids generated reach available in the sources of supply of surface or ground water used for human consumption . The volume of this liquid generation , the level of toxicity depends on the presence of organic compounds and pathogenic load virtual human body , can reach 40 liters per adult weight of 70 kilos . Its constitution comprising 60% water , 30% minerals and 10% of complex substances, little known , such as putrescine, cadaverine, etc. . This article tries to give some guidelines to serve as a guide for an Environmental Impact of a project concerning the construction of the Ecological Park Cemeteries type containing both type graves underground as niches. This is a contribution I make considering the limited literature in this country on the subject and hopefully useful to all professionals who are engaged in this type of study as well as public and private entities that develop environmental issues.